Childfree dan Implikasinya dalam Masyarakat - Siti Fatimah; Padilatul Ilmi; Jesika Indriani; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The Childfree phenomenon is a legitimate lifestyle choice for some married couples who choose not to have children. This decision can be based on various reasons, including economic factors, career, and personal freedom. Childfree allows couples to focus on their personal lives and careers, as well as enjoy greater freedom and flexibility. This choice should be respected and understood as part of individual life diversity. This study uses a literature review approach to examine the Childfree phenomenon, which is the decision of married couples not to have children. Through in-depth collection and analysis of various literature sources, including books and journals, this study aims to gain a comprehensive understanding of Childfree and the factors that influence this decision. Thus, this study can contribute to the development of knowledge and understanding of Childfree and its implications for society. Childfree is a legitimate choice that needs to be understood and respected. Couples choose Childfree due to economic, cultural, past trauma, work, health, and personal desire factors. This decision can provide freedom and marital satisfaction, but it also has consequences that need to be considered. In the Indonesian context, Childfree is increasing and needs to be discussed further. Ultimately, Childfree is a personal choice that must